2007
DOI: 10.1029/2007jc004222
|View full text |Cite
|
Sign up to set email alerts
|

Water mass characteristics in the equatorial North Atlantic: A section nominally along 6.5°N, July 2000

Abstract: [1] In July 2000, a transatlantic conductivity-temperature-depth/hydrographic section was occupied on board the Russian R/V Akademik Ioffe in the northern equatorial region from 9°26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…The average [C ant À uC T 0 ] in the lNADW ranges from 5.4 ± 0.2 lmol kg À1 in the WB in 1993 to 8.2 ± 0.3 lmol kg À1 in the EB in 2010, and the mean [C ant À TTD] values are between 2.9 ± 0.1 lmol kg À1 in the EB in 1993 and 10.7 ± 0.3 lmol kg À1 in the WB in 2010. Once again, the pulse of LSW in the early 1990s (Lazier et al, 2002), together with the eastward branching of the DWBC (Mémery et al, 2000) and the northward cyclonic flow of the NADW into the south-eastern part of the Gambia Basin reported by Sarafanov et al (2007), could be the processes responsible for the C ant redistribution in the ER region observed during 2010. Nevertheless, no pattern could be easily described there because our estimates of [C ant ] were within the methodology uncertainty.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The average [C ant À uC T 0 ] in the lNADW ranges from 5.4 ± 0.2 lmol kg À1 in the WB in 1993 to 8.2 ± 0.3 lmol kg À1 in the EB in 2010, and the mean [C ant À TTD] values are between 2.9 ± 0.1 lmol kg À1 in the EB in 1993 and 10.7 ± 0.3 lmol kg À1 in the WB in 2010. Once again, the pulse of LSW in the early 1990s (Lazier et al, 2002), together with the eastward branching of the DWBC (Mémery et al, 2000) and the northward cyclonic flow of the NADW into the south-eastern part of the Gambia Basin reported by Sarafanov et al (2007), could be the processes responsible for the C ant redistribution in the ER region observed during 2010. Nevertheless, no pattern could be easily described there because our estimates of [C ant ] were within the methodology uncertainty.…”
Section: Resultsmentioning
confidence: 90%
“…The lNADW layer is delimited by r 2 = 37.0 kg m À3 and r 4 = 45.9 kg m À3 (Johnson, 2008) and is characterized by waters that are progressively colder ($2-3°C) than uNADW. The AABW layer encloses waters below r 4 = 45.9 kg m À3 (Rhein et al, 1998;Sarafanov et al, 2007).…”
Section: Regions and Water Mass Layers Of The 75°n Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3e and 4e). Previous studies have also shown that at 7.5 • N in the Atlantic, warming occurred in the intermediate layer (500-2000 m) through comparison of hydrographic data measured in 1957(Arhan et al, 1998Sarafanov et al, 2007Sarafanov et al, , 2008, and a significant decrease in the northward AAIW transport at this latitude (Hernández-Guerra et al, 2014). Schmidtko and Johnson (2012) further showed warming and salinification trends in the AAIW core in the tropical North Atlantic since the mid-1970s.…”
Section: Discussionmentioning
confidence: 87%
“…3e and 4 e). Previous studies have also shown that at 7.5° N in the Atlantic, warming occurred in the intermediate layer (500-2000 m) through comparison of hydrographic data measured in 1957(Arhan et al, 1998Sarafanov et al, 2007Sarafanov et al, , 2008, and a significant decrease of the northward AAIW transport at this latitude (Hernández-Guerra 5 et al, 2014). Schmidtko and Johnson (2012) further showed warming and salinification trends of the AAIW core in the tropical North Atlantic since the mid-1970s.…”
Section: Conclusion 30mentioning
confidence: 99%